STUDY ON PARTICULAR FEATURES OF RUSSIAN INNOVATIVE INDUSTRIAL CORPORATIONS DEVELOPMENT AND FUNCTIONING - A. A. Astakhov; K. B. Dobrova (Модернизация, инновация, развитие, 2016)
Owing to globalization and world economic crisis consequences, present stage of economic development of Russian industrial corporations presumably belonging to the military industrial complex and to the high-tech sector of economy is characteristic with toughened competition.At the same time, these industrial enterprises endure fundamental transformations aimed at manufacture of innovative production. Under these conditions, a scientific/methodological deficiency formed in the field of financial and economic management of the corporations. Key problems are discussed whose solution may facilitate working out specialized organizational and economic strategic management mechanism for innovative development of the corporations.